Saliency Prediction in 360º Videos with Transformers - Vallejo Domínguez, Mateo (Jornada de Jóvenes Investigadores del I3A, 2023)
We present a model for saliency prediction in 360º videos based on the Transformer architecture. Our model leverages the global attention mechanism in order to represent the temporal dependencies that drive human attention. We compare our model with a current state-of-the-art model and outperform it for all metrics measured.